Physiological functions of malate shuttles in plants and algae. (May 2022) - Dao, Ousmane; Kuhnert, Franziska; Weber, Andreas P.M.; Peltier, Gilles; Li-Beisson, Yonghua
Abstract : Subcellular compartmentalization confers evolutionary advantage to eukaryotic cells but entails the need for efficient interorganelle communication. Malate functions as redox carrier and metabolic intermediate. It can be shuttled across membranes through translocators. The interconversion of malate and oxaloacetate mediated by malate dehydrogenases requires oxidation/reduction of NAD(P)H/NAD(P) + ; therefore, malate trafficking serves to transport reducing equivalents and this is termed the 'malate shuttle'. Although the term 'malate shuttle' was coined more than 50 years ago, novel functions are still emerging. This review highlights recent findings on the functions of malate shuttles in photorespiration, fatty acid β-oxidation, interorganelle signaling and its putative role in CO2 -concentrating mechanisms. We compare and contrast knowledge in plants and algae, thereby providing an evolutionary perspective on redox trafficking in photosynthetic eukaryotes. Highlights: The malate shuttle, as a valve for photosynthetic electron dissipation, has been proposed for >50 years, but only recently has this function been clearly demonstrated. The plastidial NAD-MDH is essential for embryogenesis and chloroplast development. This role is not due to its enzymatic activity but rather to its ability to stabilize a large AAA-ATPase complex at the inner envelope. The plNAD-MDH is therefore a moonlighting protein. The malate shuttle connects fatty acid biosynthesis in the chloroplast to mitochondrial reactive oxygen species (ROS) production and to programmed cell death in plants. The malate shuttle connects fatty acid catabolism in the peroxisome to photosynthesis and chloroplast metabolism in algae. Expression of malate shuttle components is responsive to CO2 levels. The latest results indicate its critical role in plant photorespiration and points to a possible role in the algal CO2 -concentrating mechanism.